2014
DOI: 10.1016/j.conb.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation by acetylcholine: examples from schizophrenia and depression

Abstract: The contribution of acetylcholine to psychiatric illnesses remains an area of active research. For example, increased understanding of mechanisms underlying cholinergic modulation of cortical function has provided insight into attentional dysfunction in schizophrenia. Acetylcholine normally enhances cortical sensitivity to external stimuli and decreases corticocortical communication, increasing focused attention. However, increases in ACh signaling can lead to symptoms related to anxiety and depression. For ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(102 citation statements)
references
References 89 publications
1
101
0
Order By: Relevance
“…Our demonstration of increases in false alarms, resulting from ill-timed cholinergic transients generated during noncued trials, illustrates the potential role of cholinergic dysregulation in the perceptual and cognitive impairments of neuropsychiatric and neurodegenerative disorders (40)(41)(42). Relatively subtle perturbations of the dynamics of cholinergic transients may alter large-scale network operations, such as fronto-parietal oscillatory activity (43), and thereby cause invalid perceptions and cue-oriented behavior (44,45).…”
Section: Discussionmentioning
confidence: 67%
“…Our demonstration of increases in false alarms, resulting from ill-timed cholinergic transients generated during noncued trials, illustrates the potential role of cholinergic dysregulation in the perceptual and cognitive impairments of neuropsychiatric and neurodegenerative disorders (40)(41)(42). Relatively subtle perturbations of the dynamics of cholinergic transients may alter large-scale network operations, such as fronto-parietal oscillatory activity (43), and thereby cause invalid perceptions and cue-oriented behavior (44,45).…”
Section: Discussionmentioning
confidence: 67%
“…Both cholinergic and serotoninergic systems, for example, can activate rapid excitatory postsynaptic potentials in postsynaptic targets through nicotinic and 5HT 3A receptors, respectively [44–46] (see also Higley and Picciotto in this issue [83]). In cortical networks, these receptors are often (but not exclusively) located on particular subpopulations of GABAergic interneurons [47,48] (see also Wester and McBain in this issue [84]) and considerable effort has been recently applied to understand the roles of these pathways (see below).…”
Section: Neurotransmitter Systems Involved In State Controlmentioning
confidence: 99%
“…Anatomical and functional evidence suggests that most of these receptors have a presynaptic and/or preterminal localisation, and modulates the release of almost all neurotransmitters, but some also have a somatodendritic post-synaptic localisation (Albuquerque et al, 2009;Gu and Yakel, 2011). In brain, the nAChRs regulate the release of both excitatory and inhibitory neurotransmitters, as a consequence, the activation of nAChRs can have opposite modulatory effects on the same circuit depending on whether they are expressed on excitatory or inhibitory neurons (Jensen et al, 2005;Albuquerque et al, 2009). nAChRs and nicotinic mechanisms contribute to cognitive function and their decline or dysfunction has been observed in several neuropsychiatric diseases (Lewis and Picciotto, 2013 ; Higley 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 and Picciotto, 2014). In addition, genetic studies have linked nAChRs to epilepsy and schizophrenia, and studies of mutant (knock-out, Ko, or knock-in, Kin) mice have shown that they are involved in pain mechanisms, anxiety depression and nicotine addiction (Picciotto et al, 2001;Champtiaux and Changeux, 2002;Gotti and Clementi, 2004;Changeux, 2010b;Drenan and Lester, 2012;Hurst et al, 2013).…”
Section: Introductionmentioning
confidence: 99%